Synonymization of the monotypic genus Nycticalanthus in Spiranthera (Rutaceae: Galipeinae) - Brito, Lilian De Andrade; Dias, Pedro; Pirani, José Rubens (Phytotaxa, 2019)
The neotropical genus Nycticalanthus Ducke (1932: 341) belongs to Rutaceae and was described by Ducke in 1932. It was based on a single species (N. speciosus Ducke [1932: 341]) with no further species described subsequently. Therefore, it still is a monotypic genus. Nycticalanthus was morphologically characterized by its shrubby to arborescent habit, with alternate, trifoliate leaves; inflorescences in terminal panicles with long pedunculated cymes; pentamerous flowers with tubular calyx, petals free and unequal to each other, five free, ascending stamens with oblong-linear anthers, disk urceolate with crenate-undulate margin, stigma shortly capitate, ovary divided in five locules with two ovules in each locule and gynophore obconic-elongated; fruit schizocarp, composed by two or three follicles, each bearing a single oblong seed (Ducke 1932).